2010
DOI: 10.1097/brs.0b013e3181cd2cb8
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain After Lumbar Discectomy in Patients Showing Endplate Modic Type 1 Change

Abstract: Discectomy improved low back pain in patients suffering from lumbar disc herniation. Patients with or without Modic type 1 change showed a similar improvement of low back pain score. Low back pain in patients with disc herniation appears to mainly originate from disc or nerve root compression, and decompression surgery without fusion is an option for these patients, even those with Modic type 1 changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 13 publications
2
62
2
2
Order By: Relevance
“…In ten studies the patients underwent microdiscectomy [11,3638,41–43,45,47,50]. Six studies documented that the patients were treated with standard open discectomy [32,34,40,44,48,49]. Two studies [16,51] included patients who were operated both with and without a microscope.…”
Section: Resultsmentioning
confidence: 99%
“…In ten studies the patients underwent microdiscectomy [11,3638,41–43,45,47,50]. Six studies documented that the patients were treated with standard open discectomy [32,34,40,44,48,49]. Two studies [16,51] included patients who were operated both with and without a microscope.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have evaluated the influence of Modic changes on improvement of LBP after lumbar microdiscectomy; Chin et al [11] found a trend toward greater improvement in patients without any MC. Ohtori et al [12] recently compared outcomes after microdiscectomy amongst patients with or without MC I, but found no statistically significant difference. These studies were probably underpowered and smoking habits were not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with CLBP and MC I changes are operated with total disc replacement [10,11]. It has also been suggested that MC I is associated with hypermobility which could indicate the need for additional fusion surgery amongst these patients [12]. Previous studies with small smaples evaluating a possible association between MC and reduced recovery of back pain after lumbar microdiscectomy present conflicting results [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…New type I and new type II conversions have been associated to the occurrence of low back pain and unfavourable outcomes in patients affected by lumbar disc herniation [8] and after lumbar discectomy [12], respectively. However, such correlation is still controversial among studies [12,14,15].…”
Section: Discussionmentioning
confidence: 99%